The Influence Of Brand Image And Beauty Trends On Gen Z Interest In Using Glad2glow Skincare In Bengkulu City - Nata, Fandwi; Hanila, Siti; Astuty, Kamelia (Jurnal Pakar Manajemen, 2026)
The purpose of this study is to examine the influence of brand image dan tren kecantikan on the purchase intention of Gen Z in using Glad2Glow skincare in Kota Bengkulu. This research is a quantitative descriptive study. The sampling method used is probability sampling with a simple random sampling design. Data collection was conducted using a questionnaire with a sample of 96 respondents.Statistical test results show that the variable brand image (X1) has a t-value of 8.781, which is greater than the t-table value of 1.986 with a significance of 0.000 (< 0.05), indicating that brand image has a positive and significant effect on the purchase intention of Gen Z using Glad2Glow skincare in Kota Bengkulu. The variable tren kecantikan (X2) also shows a t-value of 6.141, greater than the t-table value of 1.986 with a significance of 0.000 (< 0.05), indicating a positive and significant partial effect on purchase intention. The F-test shows an F-value of 361.121 with a significance of 0.000 (< 0.05), meaning both variables simultaneously have a significant effect on purchase intention. The coefficient of determination (R²) of 0.78 indicates that 78% of the variation in Gen Z's purchase intention can be explained by brand image dan tren kecantikan, while 22% is influenced by other factors. The very small significance value strengthens the validity of this regression model, making it reliable for further analysis and as a basis for Glad2Glow’s marketing strategy in the Kota Bengkulu market.